Determinación de la distribución espacial e importancia social de la flora nativa medicinal del jardín botánico San Francisco - Ramírez Pérez, Aner (2014)
In the present investigation work for the detennination of the spatial distribution of medicinal plants and its social importance of the existing native plants in the San Francisco Botanical Garden, specific objectives were raised as to quantify and characterize to the level of genus/species native flora medicinal, determine their distribution in the area that includes the botanical garden as well as their abundance; and determine its social importance of the environment by its use for the treatment of illness through the ancestral knowledge. It was achieved to detennine the spatial distribution of these medicinal species, his density, :frequency, abundance, as well as his social impact that the same one generates in the settlers of the environment. For identification were used 05 rectangular Sampling units of 200 m2 c/u, located in such a way as to coverage is more wooded area; then with the help of a specialist in forest science is proceeded to their identification, numbering, labeled referencing and records of the same; for the calculation of the spatial distribution, :frequency, density, abundance is taken into account the formulas set forth in the Guidelines for the pr~pªra.tion Qf th~ overa.ll Plan fQr FQr~st Man@g~m~nt (PGMF) ~sta.blish~d by th~ Agriculture Ministry. The results obtained were identified a total (151 units) of species identified in the San Francisco Botanical Garden only 03 of these specíes are found within the 24 most important and most used as are the "Sangre de Grado" Croton lechleri Whose abundance is equivalent to 17.2 %, the "oje" Ficus anthelmintica whose abundance is 2.6 %, as well as the "Ayahuasca" Banisteriopsis caapi with an abundance of0.6 %; the greater abundance of medicinal plants is of the species "Mucura call" Petiveria alliacia with a 21.7 %. Ofthe total surface area ofthe Botanical Garden S. F. (25,000.00 m2), the medicinal species are distributed in a 63.6 %, reaching densities of0,235 units/m2 in